Study on Fish Ecology of the Seti Gandaki River Pokhara: II. Spatio-Temporal Variations in Fish Communities - Pokharel, KK (Nepal Journal of Science and Technology, 2012)
Present paper deals with the spatio-temporal variations in distribution and abundance of fishes along the 30 km stretch of the Seti Gandaki river and its two major tributaries, Mardi Khola and Vijaypur Khola, in Pokhara Valley, Western Nepal. A total of 30 species of fishes belonging to 5 orders, 9 families and 22 genera were recorded from five sites on the river and its tributaries. Cyprinoids were predominant among fishes (17 spp.), siluroids (5 spp.), balitorids and cobitids (4 spp.), channioids (2 spp.), belonoids (one sp.) and mastacembeloids (one sp.). Among cyprinoids, mostly cyprinines were dominant groups (7 spp.) followed by rasborines (7 spp.), garrines (2 spp.) and schizothoracines (one sp.). There was increasing trend of species richness at upstream site (17 spp.). to downstream site (20 spp.) showing a longitudinal pattern. The total fish abundance and family-wise abundance at all the sites observed major peak during the spring and fall during the winter season in both the years of study. The average total density of fishes during the spring peak was highest (51.07/ha) at the upper tributary site and lowest (24.69/ha) at the urban site. According to the distribution pattern and abundance, the population status of the gamefish, mahseer [Tor tor (Ham)] has been endangered (E); that of game fishes [Tor putitora (Ham.) and Chagunius chagunio (Ham.)] and Zebra-fish [Brachydanio rerio (Ham.)] to are vulnerable (V); that of loach [Lepidocephalus guntea (Ham.)], cat-fishes [Myersglanis blythii (Day) and Amblyceps mangois (Ham.)] are rare (R). DOI: http://dx.doi.org/10.3126/njst.v12i0.6523 Nepal Journal of Science and Technology 12 (2011) 350-357